2019
DOI: 10.1186/s13256-019-2198-1
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy – eliminated and forgotten: a case report

Abstract: Background Leprosy is a disease that was declared eliminated in 2010 from Nepal; however, new cases are diagnosed every year. The difficulty arises when the presentation of the patient is unusual. Case presentation In this case report we present a case of a 22-year-old Tamang man, from the Terai region of Nepal, with a clinical presentation of fever, malaise, and arthralgia for the past 2 weeks with hepatosplenomegaly and bilateral cervical, axillary, and inguinal lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Study done by Chow et al in several developing countries showed infection the most common cause compared to other cause such as malignancy (2%-12%), collagenvascular (2%-21%), miscellaneous noninfectious (2%-50%), and unknown (12%-29%). 2,3 Since the child had a history of weight loss, low-grade fever for months, TB was one of the differential diagnoses. Positive Mantoux test and high ESR further strengthened the possibility of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Study done by Chow et al in several developing countries showed infection the most common cause compared to other cause such as malignancy (2%-12%), collagenvascular (2%-21%), miscellaneous noninfectious (2%-50%), and unknown (12%-29%). 2,3 Since the child had a history of weight loss, low-grade fever for months, TB was one of the differential diagnoses. Positive Mantoux test and high ESR further strengthened the possibility of TB.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico de lepra en áreas no endémicas suele ser dificultoso, ya que la sospecha clínica no es de primera intención. La OMS ha facilitado lineamientos que puedan facilitar la presunción diagnóstica, entre los que se encuentran: (i) pérdida sensitiva permanente de un área hipopigmentada o eritematosa, (ii) engrosamiento de un nervio periférico asociado a pérdida sensitiva, o (iii) presencia de bacilos ácido-alcohol resistentes en un frotis de piel raspada [6,7] .…”
Section: Introductionunclassified